Relative rates of B meson decays into psi(2S) and J/psi mesons - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Bellantoni, L.; et al. (Amer Physical Soc, 2009)
We report on a study of the relative rates of B meson decays into psi(2S) and J/psi mesons using 1.3 fb(-1) of p (p) over bar collisions at root s = 1.96 TeV recorded by the D0 detector operating at the Fermilab Tevatron Collider. We observe the channels B(s)(0) -> psi(2S)phi, B(s)(0) -> J/psi phi, B(+/-) -> psi(2S)K(+/-), and B(+/-) -> J/psi K(+/-) and we measure the relative branching fractions for these channels to be B(B(s)(0) -> psi(2S)phi)/B(B(s)(0) -> J/psi phi)=0.53 +/- 0.10(stat)+/- 0.07(syst)+/- 0.06(B), B(B(+) -> psi(2S)K(+))/B(B(+) -> J/psi K(+))=0.63 +/- 0.05(stat)+/- 0.03(syst)+/- 0.07(B), where the final error corresponds to the uncertainty in the J/psi and psi(2S) branching ratio into two muons.